Education, pandemic and technology: Didactic propositions for portuguese language teaching in a remote context - Balieiro , Luan Tarlau (Seven Editora, 2023)
Considering the pandemic caused by covid-19 in 2020, which implied changes in the didactic propositions in classes of Basic Education, the problematization that there are teachers with little domain of educational software became evident. In this sense, we discuss digital literacy practices, such as the production of an e-book with the Canva tool. The main objective is to reflect about the importance of teachers inserting Digital Information and Communication Technologies (ICT) in their pedagogical actions in remote teaching context. Specifically, it seeks to: understand the characteristics of digital literacy; present a didactic proposition that involves this form of literacy and which the teacher can appropriate in a remote class. Methodologically, the approach is qualitative and supported by bibliographic research. This proposition contemplates an e-book produced, through Canva, whose content is about linguistic variations, to be worked on in High School. The results show that, by producing e-books, the teacher can be motivated to explore the resources available through this tool. We conclude that the production of an e-book through Canva is an experience that encourages teachers to use the potential of ICTs in remote teaching contexts as literate subjects. DOI:https://doi.org/10.56238/alookdevelopv1-098